TINGKAT KERACUNAN BESI DALAM BENTUK FERRO DAN FERRI SERTA PERTUMBUHAN TANAMAN PADI (Oryza sativa.L) PADA MEDIA PASIR - Mimien Hariyanti; Herviyanti Herviyanti; Hermasah Hermansah (Jurusan Tanah Fakultas Pertanian Universitas Andalas, 2004)
The Recent ricefield on marginal land such as Ultisol and Oxisol has low productivity due to Fe-toxicity for rice plant (Oryza sativa.L). Flooded ricefield has reduced Ferri (Fe3+) form into Ferro (Fe2+) from which is easy to dissolve and can be toxic for plant growth. This research was aimed to determine Fe concentration that causes toxic for rice growth on sand medium either under flooded or unflooded condition. Iron was applied in form of FeSO4 at 10 levels (0, 2, 4, 8, 16, 32, 64, 128, 256, 512 ppm). Based on laboratory analyses and visual symptoms, it was found that Fe toxicity was started at Fe concentration 128 ppm. Form of Fe which is toxic to this rice plant was ferro (Fe2+) because this form is active in plant metabolism. Fe concentration at 128 ppm both conditions had shown reddish brown spot on the whole plant, therefore growth and development of plants either above or below soil surface was limited or stressed. Keywords: recent ricefield, Fe toxicity, Ferro and Ferri, brownish symptom